Sustainable Catalytic Conversion of Biomass for the Production of Biofuels and Bioproducts - Morales, Gabriel; Iglesias, Jose; Melero, Juan A. (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Biomass is widely considered as a potential alternative to dwindling fossil fuel reserves. There is a large variety of biomass sources (oleaginous, lignocellulosic, algae, etc.), with many possible conversion routes and products. Currently, biomass is not just viewed as a source of biofuels, but also as an interesting feedstock for the production of bio-based chemicals that could largely replace petrochemicals. In this context, the search for new sustainable and efficient alternatives to fossil sources is gaining increasing relevance within the chemical industry. There, the role of catalysis is often critical for the development of clean and sustainable processes, aiming to produce commodity chemicals or liquid fuels with a high efficiency and atom economy. This book gathers works at the cutting edge of investigation in the application of catalysis, for the sustainable conversion of biomass into biofuels and bio-based chemicals.